Enzymatic synthesis of some sugar-lauric acid esters by lipase from Candida antarctica and their functionalities as emulsifiers and antibacterial agents - Kangzi Ren; Guilin Chen; Ziyi Zhang; Zhao Long; Bo Zhou; Wenfang Han; Qinlu Lin (Food Chemistry: X)
To investigate the regioselectivity of lipase-catalyzed synthesis of important sugar-laurate esters and their functionalities as emulsifiers and antimicrobial agents, glucose, galactose, mannose, maltose and trehalose were used. 6-O-lauryl glucose (Glu-L), 6-O-lauryl galactose (Gal-L), 6-O-lauryl mannose (Man-L), 6′-O-lauryl maltose (Mal-L) and 6-O-lauryl trehalose/6’-O-lauryl trehalose (Tre-L) were synthesized using lipase from Candida antarctica. The Glu-L and Man-L achieved the highest yields (65.49 % and 58.16 %, respectively). The synthesized esters produced smaller-particle-size (1.9–3.1 μm), but less stable emulsions than the commercial sucrose esters (4.2–8.1 μm). The zeta-potential data revealed Man-L and Gal-L had higher surface coverage than the Glu-L on the oil droplets, while the Mal-L and Tre-L had similar surface coverage. The Man-L, Mal-L and Tre-L demonstrated the superior foamability and foam stability. The Gal-L, Man-L, Mal-L, and Tre-L inhibited E.coli 12024 (MIC 1–4 mg/mL), while only Man-L, Mal-L, and Tre-L inhibited B.subtilis 5009 (MIC 0.5–2.0 mg/mL).